Contribution to the knowledge of the butterfly fauna of the Republic of Macedonia (Lepidoptera: Papilionoidea & Hesperioidea) - Verovnik, Rudi (Acta entomologica slovenica (Ljubljana), 2010)
A faunistic account of 121 observed species of butterflies is given for the territory of Republic of Macedonia during the first week of June. Despite short period of the time large part of Macedonia was surveyed and several interesting observations were made. Among these new sites for some rare species like Melitaea arduinna, Spialia phlomidis, Gegenes nostrodamus, Coliascaucasica, Satyrium pruni, Satyrium w-album, Tarucus balkanicus, Cupido alcetas, and Araschnia levana should be mentioned. Melitaea telona is reportedfor the first time for Macedonia. The lack of faunistic surveys and priorities in butterfly conservation in Macedonia are stressed.
Keywords: entomologija; Makedonija; Metulji; ogrožene vrste; Republic of Macedonia